Assessment of Oxidative Stress in Hepatitis C Patients Receiving Interferon Therapy - Arif Malik; Muhammad Saeed Qureshi; Abdul Manan; Saadia Saleem; Mamoona Munir; Atiya Fatima; Mahwish Arooj; Muhammad Husain Qazi (ziauddin University, 2024)
ABSTRACT Background: Oxidative stress and antioxidative status caused by hepatitis C therapy plays a significant role in aggravating the disease. A number of reactive oxygen species are responsible for the damaging of cell machinery and ultimately disturbing the homeostasis of the cell. Objectives: To assess enzymatic, non-enzymatic antioxidants and circulating biomarkers in HCV patients receiving interferon therapy. Methods: Study subjects were divided into two groups; patients and controls. The levels of the Thiobarbituric acid reactive substances (TBARS, as a marker of lipid peroxidation), superoxide dismutase (SOD), glutathione (GSH), catalase (CAT) and lipid peroxidation product (MDA) in the serum were estimated. Results: There was statistically difference between patients and healthy controls in levels of CAT(p< 0.000**), SOD( p< 0.000**), GSH (p< 0.000**)and MDA(p< 0.000**). Similarly, the levels of ALT (p< 0.048*), AST (p< 0.005*) and ALP (p< 0.000**) were also statistically different between two groups. 1 Arif Malik Institute of Molecular Biology and Biotechnology, University of Lahore. 2 Muhammad Saeed Qureshi Department of Biochemistry, Allama Iqbal Medical College, Lahore. 3 Abdul Manan Institute of Molecular Biology and Biotechnology, University of Lahore. 4 Saadia Saleem Institute of Molecular Biology and Biotechnology, University of Lahore. 5 Mamoona Munir Institute of Molecular Biology and Biotechnology, University of Lahore. 6 Atiya Fatima Institute of Molecular Biology and Biotechnology, University of Lahore. 7 Mahwish Arooj Center for Research in Molecular Medicine, University of Lahore. 8 Muhammad Husain Qazi Center for Research in Molecular Medicine, University of Lahore. Corresponding Author Arif Malik Conclusion: Imbalanced levels of superoxide dismutase, catalase, reduced glutathione, MDA and serum enzymes (e.g. ALT, AST, ALP) revealed that interferon itself play a crucial rule in disturbing oxidative vs. antioxidative status which ultimately results in tissue damaging. Increased levels of MDA have a significant correlation with disease development during the course of therapy. KEY WORDS: ALT, AST ALP, Antioxidants, MDA (Malonyldialdehyde) Superoxide dismutase, Catalase, Reduced Glutathione.